A construção do conhecimento matemático nas experiências vivenciadas com crianças pré-escolares - Passarini, Dulcineia Mara Aparecida Moreira (2019)
This research was carried out with preschool children of a Municipal Early Childhood Education institution, in the city of Piracicaba, and aimed to identify relationships of playing with mathematical knowledge, promoted from the experiences experienced with children in everyday life and in the games of Early Childhood Education, being guided by the following question: What mathematical knowledge is built from the experiences experienced with children in preschool phase? For this, it was used the qualitative research as a methodological basis with the design of a case study from the pedagogical project "The construction". This was born from listening to the voices, movements and gestures of children during the play with pieces of wood, recognized as unstructured material. The data were produced by means of observation, recording, reflection and discussions of those involved during the elaboration and execution of this project. To analyze the data, we opted for data triangulation: children's speeches recorded in the researcher's field diary, implementation of the pedagogical project and observations of the experiences with the children. After establishing the triangulation of the data produced during the research, two categories of analysis were listed from the problem issue, a priori, and the emergence of the case study, a posteriori: The involvement of children during the experiences with civil construction and the mathematical knowledge present in the experiences with civil construction. The research shows the involvement of children during the experiences, since it started from the discovery of the world of construction, a curiosity initially demonstrated through play. The mathematical knowledge understood as one of the children's languages was an integral part of the possibilities experienced by children in play, involving the notions of inside and outside, greatness, correspondence one by one, and geometry. The research identified that, with the project's proposal, the children came into contact with more elaborate cultural forms in contact with plants of houses and with the construction of a barbecue, using objects suitable for this purpose during the games. Through the interactions, the children researched the objects and their possibilities in the reproduction of the characteristics of civil construction, and with the mediation of the teacher-researcher, the children came into contact with the mathematical knowledge inserted in the games, expanding the cultural repertoire on the subject.